Overview of Patient Satisfaction in the Use of the Self-Medication List Platform (Adabatman) in the Outpatient Installation of Toto Kabila Hospital - Musdin Suge; Zainuddin; Ibrahim Suleman (Universitas Muhammadiyah Palu, 2026)
The development of information technology encourages hospitals to innovate services, one of which is through the implementation of the Self-Medication List Platform (ADABATMAN) in outpatient services. This system is expected to speed up the registration process, reduce queues, and increase patient satisfaction. However, in its implementation, technical obstacles and differences in patients' abilities in using technology are still found, so it is necessary to evaluate in terms of patient satisfaction. This study aims to find out the picture of patient satisfaction in the use of ADABATMAN in the Outpatient Installation of Toto Kabila Hospital based on the dimensions of reliability, assurance, tangibles, empathy, and responsiveness. Research method This study uses a quantitative method with a descriptive design. The research sample amounted to 84 respondents who were selected using accidental sampling techniques. Data were collected using a questionnaire based on the SERVQUAL (RATER) model and analyzed univariately to see the distribution of patient satisfaction levels. The results showed that most patients were satisfied with the use of ADABATMAN. In the reliability and responsiveness dimensions, the majority of respondents expressed satisfaction because the system was considered quite fast and helped the registration process. The assurance dimension shows a good level of satisfaction because patients feel safe and trust in the services provided. The tangibles dimension obtained the highest level of satisfaction, demonstrated by a positive assessment of the physical condition of the machine, facilities, and service environment. Meanwhile, in the empathy dimension, although most respondents were satisfied with the attitude and attention of the officers, there were still respondents who stated that they were quite satisfied, especially in elderly patients who needed more assistance when using the system. In conclusion, in general, the level of patient satisfaction with the use of ADABATMAN in the Outpatient Installation of Toto Kabila Hospital is in the satisfied category. Nevertheless, hospitals still need to improve assistance for elderly patients and carry out regular system maintenance so that the quality of technology-based services can be more optimal.